Smart buildings. - Snoonian, D. (IEEE spectrum)
Can building automation systems overcome interoperability problems to assert control over our offices, hotels, and airports? Efforts to make buildings smarter are focusing on cutting costs by streamlining building operations like air conditioning and lighting. Building automation is critical to these efforts, mainly because it could reduce the annual operating costs of buildings. This article outlines the latest building automation systems including the BACnet and LonWorks that integrate the services.